HUBUNGAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA UMUR 24-59 BULAN DI PUSKESMAS SIKABU LUBUK ALUNG - Nelli, Septa; Eliza, Eliza; Syofrul, Bunga Permata (Ensiklopedia of Journal, 2024)
Stunting is a condition of failure to thrive that occurs in toddlers. stunting is caused by inadequate nutritional intake for a long time due to the provision of food that is not in accordance with WHO nutritional needs), stated that around 150.8 million children under five died due to stunting. The number of stunting children in Indonesia has increased from 27.5% in 2016 to 29.6% in 2017. West Sumatra Health Office in 2018-2021 The prevalence of short toddlers according to TB/U is 2018 (30.8% ), in 2019 (27.7%) and in 2021 (24.4%) the Padang Pariaman District Health Office, with an incidence rate in the last 3 months of 2022 as many as 83 cases at the age of 24-59 months. This study aims to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers at the Sikabu Health Center. This type of quantitative research with a Cross Sectional Study approach. The research was conducted on 1 July-31 August 2022 at the Sikabu Health Center. The research sample was 83 people. Sampling by means of Total Sampling. Statistical test using Chi Square degree of significance (p value < 0.05). The results showed that most (81.9%) mothers who had infants under five gave exclusive breastfeeding until they were 6 months old. Most (80.7%) mothers who have toddlers aged 24-59 months do not experience stunting. There is a significant relationship between breastfeeding and the incidence of stunting at the Sikabu Health Center in 2022 with a p value = 0.000 (p value < 0.05). After doing this research, it is hoped that mothers and their families will be aware of the importance of exclusive breastfeeding.Keywords: Exclusive Breastfeeding, Stunting